Idiopathic spontaneous uterine rupture - a case report - Omar, NS; Mat Jin, N; Ahmad, ZA; Wan Nordin, N; Abas, Razif (The Ministry of Health and Universiti Brunei Darussalam, 2024)
Uterine rupture during pregnancy is rare but a catastrophic event. It is more common in a scarred uterus compared to an unscarred uterus. We report a case of rupture of an unscarred uterus in the second trimester with no known risk factors and emphasise awareness of this condition and immediate intervention for achieving a better prognosis.